Pengaruh Disiplin, Pendidikan Dan Pelatihan, Job Description, Skill Dan Komunikasi Terhadap Kinerja Karyawan (Studi Kasus Pada PT. Surya Toto Indonesia, Divisi Saniter, Unit Cikupa, Tangerang) - Jaka Slameta; Titik Sulastri (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2023)
This This research aims to determine the direct influence, indirect influence and total influence between Discipline, Education and Training, Job Description, Skills and Communication on Employee Performance (Case Study at PT. Surya Toto Indonesia, Sanitary Division, Cikupa unit, Tangerang). The data used is primary data obtained from distributing questionnaires to 343 respondents who are employees of PT. Surya Toto Indonesia, Sanitary division, Cikupa unit, Tangerang. The analysis method used is path analysis using the SPSS Version 20.0 program. The results of the analysis state: variables X1 (Discipline), X2 (Education and Training), X4 (Skills) and X5 (Communication) are significantly correlated with endogenous variables, namely: PT Employee Performance. Surya Toto Indonesia, Sanitary Division, Cikupa unit, Tangerang and produced the structural equation Y = 0.172 The direct influence, indirect influence and total influence of variables X1 (Discipline), X2 (Education and Training), X4 (Skills) and SPSS. The research results show that the total influence of X1 (discipline) on Y (employee performance) is 0.0648 or 6.48%. The total influence of X2 (education and training) on ​​Y (employee performance) is 0.0739 or 7.39%. The total influence of X4 (skill) on Y (employee performance) is 0.0735 or 7.35%. The total influence of X5 (communication) on Y (employee performance) is 0.1801 or 18.01%. The total influence of X1 (discipline), X2 (education and training), X4 (skills) and X5 (communication) on the performance of PT employees. Surya Toto Indonesia unit Cikupa, Tangerang, was 0.393 or 39.3%